Pilgrimage and the Passage to Self - Lahoski, Beth (Analecta Malacitana. Revista de la sección de Filología de la Facultad de Filosofía y Letras, 2024)
«Pilgrimage» implies a journey made by those in movement towards a specific location or site. When defined strictly in Christian terms, the destination chosen limits itself to a sacred or holy place, many times a sanctuary or temple where the presence of the saint or «invisible friend», in the words of Peter Brown, is felt and sought after, the intercessor thus serving as the connection to the celestial realm. While the association of sacredness often rests upon a pilgrimage destination, this paper seeks to explore the «passage» or the road itself as a hierophany which erupts into the mundane, leading the pilgrim to the sacred. This concept of hierophany highlighted in Miceau Eliade’s works demonstrates how the sacred breaks into the human experience, in this case, pilgrims walking along the road or «passage» which is leading them onwards and upwards, thus parallel to the joyous proclamation of «Ultreia et Suseia». By stepping upon this pilgrimage road, the traveler is able to connect and experience the transcendent while simultaneously discovering true self. The aim of the paper is to show the connection of the pilgrimage road as a passage and to reveal how through pilgrimage there is a return to self, as one is uncovering identity whilst making his or her way along the road. With this in mind, concepts from Zygmunt Bauman’s studies will also be addressed and two texts will be reviewed, both by female travelers from the United States who, at the turn of the twentieth century, ended up on the Santiago pilgrimage road in Spain, all of which will be instrumental in order to evidence this phenomenon. These women, whose journeys led them to the passage of self, reveal how the Santiago road and shrine either was or became a focal point of their sojourns, evident in the pages of their narratives. Setting out upon the sojourn signifies that the pilgrim is away from home, experiencing the unfamiliar and embracing encounters upon a path, or a «passage» which is the liaison to the sacred, enabling the discovery and formation of self and therefore constructing identity. Although more than a century has passed, this same feature of the Santiago pilgrimage road continues to act upon female sojourners of the 21st century.